Does Induction of Labor Increase the Risk of Cesarean Section? A Systematic Review and Meta-Analysis of Trials in Women With Intact Membranes. Issue 2 (June 2015) - Wood, S.; Cooper, S.; Ross, S.
Abstract : ( BJOG . 2014;121(6):674–685)